The spirit of the Appalachian Trail : community, environment, and belief on a long-distance hiking path - Bratton, Susan (University of Tennessee Press, 2012)
"Want to know what wilderness means to people who live it for over two thousand miles? Then read this extremely interesting, informative, intelligent, and thoughtful book."--Roger S. Gottlieb, author of Engaging Voices: Tales of Morality and Meaning in an Age of Global Warming "There is no doubt that Bratton's book will be of value to students and scholars of leisure studies, recreation, and religion. Those who are familiar with the Appalachian Trail sense intuitively that a journey along its length kindles spiritual awakening; this book provides the hard data to prove it's true."--David Brill, author of As Far as the Eye Can See: Reflections of an Appalachian Trail Hiker The Appalachian Trail covers 2,180 miles, passing through fourteen states from Georgia to Maine. Each year, an estimated 2-3 million people visit the trail, and almost two thousand attempt a "thru-hike," walking the entire distance of the path. For many, the journey transcends a mere walk in the woods and becomes a modern-day pilgrimage. In The Spirit of the Appalachian Trail: Community, Environment, and Belief, Susan Power Bratton addresses the spiritual dimensions of hiking the Appalachian Trail (AT). Hikers often comment on how their experience as thru-hikers changes them spiritually forever, but this is the first study to evaluate these religious or quasireligious claims critically. Rather than ask if wilderness and outdoor recreation have benefits for the soul, this volume investigates specifically how long-distance walking might enhance both body and mind. Most who are familiar with the AT sense intuitively that a trek along its length kindles spiritual awakening. Using both a quantitative and qualitative approach, this book provides the hard data to support this notion. Bratton bases her work on five sources: an exhaustive survey of long-distance AT hikers, published trail diaries and memoirs, hikers? own logs and postings, her own personal observations from many years on the trail, and conversations with numerous members of the AT community, including the "trail angels," residents of small towns along the path who attend to hikers? need for food, shelter, or medical attention. The abundant photographs reinforce the text and enable visualization of the cultural and natural context. This volume is fully indexed with extensive reference and notes sections and detailed appendixes. Written in an engaging and accessible style, The Spirit of the Appalachian Trail presents a full picture of the spirituality of the AT. Susan Power Bratton is professor of environmental studies. She is the author of Six Billion and More: Human Population Regulation and Christian Ethics, Environmental Values in Christian Art, and Christianity, Wilderness, and Wildlife: The Original Desert Solitaire.